2010
DOI: 10.1097/scs.0b013e3181cfa7d7
|View full text |Cite
|
Sign up to set email alerts
|

Central Osteoma Associated With Root Resorption

Abstract: Osteomas of the jaws are rare osteogenic lesions considered to be true neoplasms, characterized by the proliferation of compact and/or cancellous bone. It can be central, peripheral, or of an extraskeletal type. The central osteoma arises from the endosteum, the peripheral osteoma from the periosteum, and the extraskeletal soft tissue osteoma usually develops within a muscle. However, in a previous work we have suggested that at least some peripheral osteomas may be reactive rather than neoplasms, probably ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 13 publications
0
17
1
3
Order By: Relevance
“…41 In some instances, central osteomas are not related to a tooth; however, there is evidence of central osteomas associated with root displacement or root resorption. 42 Central osteoma radiographically presents as a round radiopaque mass with well-defined borders, and with apparently no radiolucent halo between the lesion and the normal bone (Figure 3, D). 5 The three types of osteomas present the same histological characteristics, comprising the presence of mature bone with compact lamella or/and trabecular bone with sparse channels of fibrovascular tissue (Figure 3, E).…”
Section: Osteomamentioning
confidence: 99%
“…41 In some instances, central osteomas are not related to a tooth; however, there is evidence of central osteomas associated with root displacement or root resorption. 42 Central osteoma radiographically presents as a round radiopaque mass with well-defined borders, and with apparently no radiolucent halo between the lesion and the normal bone (Figure 3, D). 5 The three types of osteomas present the same histological characteristics, comprising the presence of mature bone with compact lamella or/and trabecular bone with sparse channels of fibrovascular tissue (Figure 3, E).…”
Section: Osteomamentioning
confidence: 99%
“…There has been debate whether the lesion is reactive in nature or truly neoplastic. 14,17 There was no known trauma as far as the authors are aware in the dogs examined in this study, however periodontal disease was apparent in 3 of the dogs. 5,6,9,14,16 There are a very limited number of known trauma-induced oral osteoma cases documented in the human literature.…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that studies often fail to differentiate between an osteoma (benign neoplasm) and exostosis (hamartoma). 6,11,14,16 The six cases included in this study had palpable masses with radiographic and histopathological diagnoses consistent with osteoma. 6,17,18 Thus, the clinical, radiographic, and histopathological findings must be used to accurately diagnose osteoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological image of central osteoma requires differentiation with complex odontoma and Garré's sclerosing osteomyelitis, eosinophilic granuloma and osteosarcoma [8]. Central osteomas are sometimes located near mandibular molars; in this form, they are often recognized as condensing osteitis or idiopathic osteosclerosis [9]. Treatment consists of radical surgical removal of the tumour.…”
Section: Introductionmentioning
confidence: 99%